Analyzing Metaphor Micro and Macro Translation Strategies in the Arabic Rendering of George Orwell’s 1984: تحليل استراتيجيات ترجمة الاستعارة إلى العربية في رواية جورج أورويل "1984" - ENNEBATI , Fatima Zohra; CHIKHI , Latifa (Maalim, 2026)
This paper presents a descriptive case study analyzing the metaphor translation strategies employed by Anwar Chami in his Arabic rendition of George Orwell's 1984. Applying a dual-level framework, it categorizes metaphor translation micro-procedures using the taxonomies of Newmark and Larson, and interprets these choices through Venuti's macro-strategies of domestication and foreignization. The analysis of key metaphors has revealed a hybrid approach oscillating between foreignization and domestication, where Chami consistently prioritizes communicative clarity and cultural assimilation through semantic intensification and paraphrase, often at the expense of preserving the original's precise ironic tone and estranging effect. The study has concluded that Chami’s translation functions as a selective interpretive mediation in which metaphorical choices play a decisive role in reshaping Orwell’s dystopian vision for Arab readers, confirming that metaphor translation is a key factor in determining the ideological and cultural reception of the novel across linguistic boundaries.